Green Accounting Enhances Sustainability Report Integrity: Does Governance Support Voluntary Disclosure Perspectives? - Teti Rahmawati; Amir Hamzah (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2025)
This study examines the relationship between the disclosure of Good Corporate Governance (GCG), Green Accounting (GA), Environmental Performance (EP), and Sustainability Reporting (SR) in manufacturing companies in the primary consumer sector listed on the Indonesia Stock Exchange (IDX) for the 2021 to 2023 period. Path analysis shows that GCG and GA disclosures significantly enhance SR quality directly and through EP as a mediating factor. GCG strengthens transparency and accountability in corporate governance, while GA integrates environmental considerations into financial decision-making, improving EP. EP reflects the company's commitment to sustainable practices. These findings highlight the importance of integrating GCG principles and GA practices into business strategies to improve SR quality, build stakeholder trust, and achieve long-term sustainability goals. The study provides implications for companies and policymakers to advance sustainability efforts by strengthening governance and environmental accounting practices as part of a strategic corporate framework.